Implication of Air pollution on health effects in Nepal: Lessons from global research - Kurmi, Om; Regmi, Pramod R; Pant, Puspa Raj (Nepal Journal of Epidemiology, 2016)
Correction 7th May 2016: p.256 Column 2, paragraph 3, line 7 - 'National Health Policy of Nepal (2015/16)' changed TO 'National Health Policy of Nepal (2014)'. The Nepal Health Research Council and recent National Health Policy of Nepal (2015/16) have included ‘air pollution’ as a priority research/public health agenda that is guaranteed by the Constitution. There is an urgent need to organise the future policies and actions to ensure the commitments to reduce air pollution.